1975
DOI: 10.1113/jphysiol.1975.sp011195
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane exchange of chloride with bicarbonate ion in mammalian red blood cells: evidence for a sulphonamide‐sensitive "carrier".

Abstract: SUMMARY1. It is well known that red blood cells suspended in isotonic NH4C1 solution swell because penetration of NH3 induces a transmembrane exchange between Cl-0 and OH-, (or HCO3-j). The rate of swelling thus depends on the speed of the transmembrane exchanges and on the amount of anions available for exchange.2. It has been demonstrated in experiments carried out in a C02-free medium that OH-ions are poorly permeating whereas the permeability for HCO3-is very high. Thus the rate of swelling is largely depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

1976
1976
2009
2009

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 18 publications
3
29
0
Order By: Relevance
“…AE1 bicarbonate efflux activity was maximally inhibited by 70 Ϯ 2% at an acetazolamide concentration of 250 M. The apparent K i was 54 M, which is higher than the 10 Ϫ8 M value measured using purified CAII (20). The concentration of carbonic anhydrase inhibitors required to have an effect on anion exchange in erythrocytes were also found to be several orders of magnitude higher than required to inhibit CAII (24,25). In these studies, CAII did not become rate-limiting for anion exchange until the enzyme was inhibited to greater than 99%.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…AE1 bicarbonate efflux activity was maximally inhibited by 70 Ϯ 2% at an acetazolamide concentration of 250 M. The apparent K i was 54 M, which is higher than the 10 Ϫ8 M value measured using purified CAII (20). The concentration of carbonic anhydrase inhibitors required to have an effect on anion exchange in erythrocytes were also found to be several orders of magnitude higher than required to inhibit CAII (24,25). In these studies, CAII did not become rate-limiting for anion exchange until the enzyme was inhibited to greater than 99%.…”
Section: Resultsmentioning
confidence: 90%
“…Effect of CAII Inhibition on Cl Ϫ /HCO 3 Ϫ Exchange Activity-To determine the role of CAII in facilitating AE1 transport activity, we compared the Cl Ϫ /HCO 3 Ϫ exchange activity of cells transiently transfected with AE1 cDNA before and after incubation with acetazolamide, a sulfonamide that inhibits CA enzymatic activity without direct effect on anion exchange (25,48). To measure AE1 transport activity, HEK293 cells grown on coverslips were transiently transfected with AE1 cDNA, loaded with BCECF-AM, a pH-sensitive fluorescent dye, and mounted in a fluorescence cuvette.…”
Section: Resultsmentioning
confidence: 99%
“…Acetazolamide does not affect Cl-HCO3 exchange across red cell membranes (Cousin, Motais & Sola, 1975) nor, uniquely among a wide range of carbonic anhydrase inhibitors studied, does it impair Cl-Cl self-exchange (Cousin & Motais, 1976). If these findings are applicable also to renal medullary cells, the effects of acetazolamide upon cell volume (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…It has recently been shown that benzolamide (Cl 11,366) and Cl 13,580 inhibit the transmembrane Cl-/HCO3-exchanges by acting directly at membrane level Cousin et al 1975). The present results show that the self-exchanges of organic anions (AO-/Ai-) or chloride (Cl-/Cl1-), in which carbonic anhydrase could not be involved, are also inhibited by sulphonamides.…”
Section: Discussionmentioning
confidence: 99%